Responsible Hedge Funds - Assessment of an SRI Concept - Pinner, Wolfgang (2007)
The paper in hand shows an analysis of the applicability of responsible or SRI (Socially Responsible Investment) processes to the asset class of hedge funds. One of the major findings is, that hedge fund investors obviously can create corporate social performance on top of financial performance directly in two ways. The alternatives are to give financial support on the basis of investments or to start a dialogue with the company,the engagement process. On the basis of selling shares short, responsible hedge fund are able to use an additional lever in their engagement process.